2021
DOI: 10.1155/2021/6626627
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Protects Human Endothelial Progenitor Cells from High-Glucose-Induced Senescence through B2 Receptor-Mediated Activation of the Akt/eNOS Signalling Pathway

Abstract: Background. Circulating endothelial progenitor cells (EPCs) play important roles in vascular repair. However, the mechanisms of high-glucose- (HG-) induced cord blood EPC senescence and the role of B2 receptor (B2R) remain unknown. Methods. Cord blood samples from 26 patients with gestational diabetes mellitus (GDM) and samples from 26 healthy controls were collected. B2R expression on circulating CD34+ cells of cord blood mononuclear cells (CBMCs) was detected using flow cytometry. The plasma concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…D-Glucose (G8150) and D-mannitol (M8140) were obtained from Solarbio (Beijing, China). For the studies comparing the effects of mannitol, HUVECs were incubated with different media that were defined as NG (glucose concentration of 5.5 mM), HG (40 mM) (Arunachalam et al, 2014;Wu et al, 2021), osmotic control (40 mM: 5.5 mM of glucose +34.5 mM of D-mannitol) for 48 h. The media were changed every 24 h.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…D-Glucose (G8150) and D-mannitol (M8140) were obtained from Solarbio (Beijing, China). For the studies comparing the effects of mannitol, HUVECs were incubated with different media that were defined as NG (glucose concentration of 5.5 mM), HG (40 mM) (Arunachalam et al, 2014;Wu et al, 2021), osmotic control (40 mM: 5.5 mM of glucose +34.5 mM of D-mannitol) for 48 h. The media were changed every 24 h.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Conversely, AMPK-induced senescence in endothelial cells can be prevented by increasing the levels of SIRT1 . Besides AMPK signal, recent studies have demonstrated that the serine–threonine kinase Akt is important in regulating cell senescence and telomerase activity. ,, Activation of Akt has been shown to be important in the prevention of EPC senescence by resveratrol, a SIRT1 activator . Likewise, visfatin markedly attenuates the ox-LDL-induced senescence of EPCs by upregulating SIRT1 expression and Akt signal .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have used cell proliferation, glucose consumption, ROS, TERT and SA- β -gal as biological markers to examine cell senescence. Abnormal cell viability is the main characteristics of senescent cells [ 29 32 ]. In the present study, D-gal significantly inhibited H9c2 cell proliferation and promoted apoptosis.…”
Section: Discussionmentioning
confidence: 99%